Origin and differentiation of a sex chromosome system in Parodon hilarii (Pisces, Parodontidae). Satellite DNA, G- and C-banding - Vicente, V. E.; Bertollo, LAC; Valentini, Sandro Roberto [UNESP]; Moreira, O. (Kluwer Academic Publ, 2003)
A satellite DNA sequence of Parodon hilarii ( named pPh2004) was isolated, cloned and sequenced. This satellite DNA is composed of 200 bp, 60% AT rich. In situ hybridization ( FISH) results revealed that the satellite DNA pPh2004 is located in the terminal regions of several chromosomes, forming highly evident blocks in some and punctual marks in others. The comparison between the FISH and C-banding results showed that the location of this satellite DNA coincides with that of most terminal heterochromatins. However, some regions are only marked by FISH whereas other regions are only marked by C-banding. The possible existence of more than one satellite DNA family could explain these partial differences. The in situ hybridization with the satellite DNA and the G- and C-bandings confirmed the presence of a sex chromosome system of the ZZ/ZW type in P. hilarii, as well as the correct identification of the Z chromosome in the karyotype. This chromosome displays a segment of terminal heterochromatin in the long arm, similar to the segment observed in the short arm of the W chromosome, also showing a G- banding pattern similar to that of the short arm and part of the long arm of the W chromosome. A hypothesis on the origin of the W chromosome from an ancestral chromosome similar to the Z chromosome is presented.
Keywords: C-banding; FISH; G-banding; Parodon hilarii; satellite DNA; sex chromosomes